Transformasi Lanskap: Pembukaan Perkebunan di Besuki terhadap Ekologi pada Awal Abad ke-20 - Rinda Handayani (Keraton: Journal of History Education and Culture, 2025)
This study analyzes the significant ecological transformation in the Besuki region due to plantation expansion in the early 20th century. This research reveals how Besuki, as the center of plantation production during the colonial period, experienced ecological changes such as deforestation to land clearing for settlements. This research uses historical methods to reconstruct past events. This study aims to analyze (1) how plantation activities in Besuki have changed the ecological landscape of Besuki Residency. (2) Deforestation until the emergence of settlements in Besuki Residency. Keywords: plantation, Besuki, ecology,